Acceptance Factors in Making Cryptocurrency as an Alternative Financial Tool Among Generation Y - Teck Kang Teo; Wai Mun Yeong; Malathi Nair a (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The contemporary digital era has brought about some significant changes to both the framework of traditional financial activities and the state of the world economy. Blockchain technology has transformed financial activities including investing, trade, and online payments in the present global and economic setting. Digitizing the use of money is one of the major advances in today's tech-savvy world. Regulators, bankers, innovators, investors, and consumers all around the world are interested in this new peer-to-peer payment method due to its disruptive potential. Cryptocurrency is a digital asset designed to operate as a medium of trade that relies on encryption to ensure the transactional flow and regulate the generation of new currency units. While cryptocurrencies have been successful, the lack of internal exploratory research and attention to Malaysian users has led to limited adoption of cryptocurrencies in Malaysia. Thus, it is vital to invent a new paradigm by investigating the acceptance factors since many individuals still don't know about this emerging technology. Additionally, people's propensity to adopt is influenced by how much faith they have in the technology. Thus, the study proposes to examine the adoption of cryptocurrency among Generation Y. A survey was carried out, and the framework was tested using SmartPLS to generate the results. The results found a significant impact of brand trust, behavioral attitude, and perceived usefulness towards the adoption of cryptocurrency. Additionally, the mediation role of behavioral attitude is significant between brand trust and perceived usefulness in the adoption of cryptocurrency. The limitations and recommendation of the study are further discussed.